2016
DOI: 10.14295/cs.v7i3.1095
|View full text |Cite
|
Sign up to set email alerts
|

Modelos alométricos na determinação da área foliar de Bauhinia monandra Kurz

Abstract: The aim of this study was to evaluate the efficiency of the adjustment of mathematical models for determining Bauhinia monandra leaf area using the length and/or width of the leaves as independent variables. Leaves from plants with three years were used to the estimative of equations in linear, quadratic and potential models. The validation from the estimated leaf area as a function of the observed leaf area showed that the linear model based on the product of length and width of the largest leaf surface is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The equation must be chosen not only by the high coefficient of determination (R 2 ), but by several criteria as well as performed by [25] and [15]. The criteria for the validation of the equations are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The equation must be chosen not only by the high coefficient of determination (R 2 ), but by several criteria as well as performed by [25] and [15]. The criteria for the validation of the equations are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…However, a model must not be selected only for the high value of R 2 , during the modeling, but by the interpretation of all the statistical measures of validation from an independent sample of that used for modeling (Bosco et al, 2012;Fascella, Darwich, & Rouphael, 2013;Schmildt et al, 2016;Walia & Kumar, 2017). The validation made from the sample of garden boldo leaves verified that from the 12 adjusted equations, only those that used LW as an independent variable in the linear, quadratic and power models are suitable, according to the criteria of statistically linear coefficient equal to zero and statistically angular coefficient equal to one (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In practice, the use of linear model equations based only on one dimension of the leaves is preferable due to simplicity of application, mainly on the field (Tsialtas & Maslaris, 2005), as performed by Schmildt et al (2016), who indicated the use of length of leaves in Bauhinia monandra, and by Tartaglia et al (2016), who indicated the use of width of leaves in canola. However, in relation to garden boldo leaves, none of the models was suitable using only one allometric measure, as can be seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mathematical equations to estimate leaf area has been reported for several plant species [5]- [11]. However, no literature is lack of studies that seek to model the area leaf for Cordia myxa L.…”
Section: Introductionmentioning
confidence: 99%